2020
DOI: 10.3389/fncel.2020.00261
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microglia in Perioperative Neurocognitive Disorders

Abstract: Perioperative neurocognitive disorder (PND) is a common phenomenon associated with anesthesia and surgery and has been frequently described in the elderly and susceptible individuals. Microglia, which are the brain's major resident immune cells, play critical roles in maintaining neuronal homeostasis and synaptic plasticity. Accumulating evidence suggests microglial dysfunction occurring after anesthesia and surgery might perturb neuronal function and induce PND. This review aims to provide an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…Inflammation associated with POCD involves both central and peripheral compartments 5,6 . Surgery activates an immune response and results in the release of systemic proinflammatory factors and eventually leads to neuroinflammation 7–9 . Studies have shown that microglia are activated by peripheral proinflammatory cytokines 10 and can release additional proinflammatory cytokines, exacerbating neuroinflammation and brain damage 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation associated with POCD involves both central and peripheral compartments 5,6 . Surgery activates an immune response and results in the release of systemic proinflammatory factors and eventually leads to neuroinflammation 7–9 . Studies have shown that microglia are activated by peripheral proinflammatory cytokines 10 and can release additional proinflammatory cytokines, exacerbating neuroinflammation and brain damage 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, under pathological conditions, the hippocampus is particularly vulnerable to proinflammatory factors. Therefore, the release of proinflammatory cytokines by M1‐type microglia may lead to the injury of hippocampus and eventually lead to POCD 7 …”
Section: Introductionmentioning
confidence: 99%
“…Especially, microglia are the main participants in the brain's immune response. Furthermore, microglia dysfunction that occurs after anesthesia and surgery may disrupt neuronal function and induce PND [23]. P2X4 is mainly expressed in microglia in the CNS, where this receptor is involved in various functions under physio-logical conditions [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…The release of in ammatory cytokines causes neuronal damage and amplify the in ammatory response in CNS 30 . And then, we used two types of co-culture systems according to the ideas of our predecessors [31][32][33][34] , CM co-culture system and Transwell co-culture system, to verify the neuroprotective effects of PK11195 and Midazolam.…”
Section: Discussionmentioning
confidence: 99%